The Mouse and his child - Hoban, Russell (London : Puffin, 1993)
A wind-up mouse and his child, broken and then mended, set out to find the animals and doll house with which they were in the toy shop. Along the way, they make enemies with a dump rat and have many adventures.
Keywords: Animals -- Fiction; Toys -- Fiction